2010
DOI: 10.4314/bajopas.v3i1.58550
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal toxicity studies of sub-chronic administration of calyx aqueous extracts of hibiscus sabdariffa in albino rats

Abstract: Hibiscus sabdariffa Linn has been reported to have a broad range of therapeutic effects. Subchronic effects of calyces aqueous extracts of H. Sabdariffa were studied in albino rats. Twenty four (24) albino rats were randomly divided into six (6) groups of four rats each. Group A, was fed with growers mesh and distilled water as control. Groups B to F were administered orally with the aqueous extract at 1, 2, 3, 4 and 5g /kg body weight respectively and the treatment period was 28 days. A decreased in weights o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…The previous study on water extract of rosella also found that treatment on higher dose increased the ureum and creatinine level significantly 22,23,13,15 . This finding confirms the data of toxicity of rosella extract on renal function for long duration treatment.…”
Section: The Effect Of Ethanol Extract Of Rosella On Renal Functionmentioning
confidence: 78%
See 2 more Smart Citations
“…The previous study on water extract of rosella also found that treatment on higher dose increased the ureum and creatinine level significantly 22,23,13,15 . This finding confirms the data of toxicity of rosella extract on renal function for long duration treatment.…”
Section: The Effect Of Ethanol Extract Of Rosella On Renal Functionmentioning
confidence: 78%
“…Some damage in the kidney could be in the form of necrosis, cell proliferation, inflammatory cell infiltration, and hemorrhage. Various studies have been conducted to evaluate the safety of roselle as a traditional medicine [10][11][12][13][14] . It was reported the subchronic treatment of a high dose of water extract of roselle in albino rats could affect the kidney function with parameters of urea, creatinine and uric acid 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the effects of H. sabdariffa methanolic calyx extract on the body weight, cholesterol and liver marker enzymes activities of normal male albino rats. The decrease in the values on body weight when Olatunji et al (2005) observed no significant decrease in body weight among rats that were chronically treated with 25 and 50 mg/kg The loss of appetite in the treated animal models due to daily administration of H. sabdariffa extracts had previously been suggested (Abubakar et al, 2010;Orisakwe et al, 2003). This reduction in the body weight could also be directly attributed to the observed hypocholesterolemic property of this extract, owing to the fact that cholesterol significantly contributes to the total fat content of an individual.…”
Section: Discussionmentioning
confidence: 94%
“…Liver and kidney indices (AST, ALT, ALP, and direct bilirubin) significantly increased, indicating organ dysfunction, when 1-5 g/kg of calyx extracts of HS was fed to rats. Furthermore, at dose levels of 2, 3, 4, and 5 g/kg, the levels of creatinine, urea, and uric acid increased significantly compared to the control group [129]. Conversely, [130] reported that extracts of HS did not manifest acute toxicity in Sprague-Dawley (SD) rats even at an amount of 5000 mg/kg body weight.…”
Section: Toxicological Aspectmentioning
confidence: 98%